Research and application of RFID location algorithm based on reference tags - WANG Yuan-zhe1; MAO Lu-hong1; LIU Hui1; XIAO Ji-gao1 (Tongxin xuebao)
Several improvements of the existing reference tag-based nearest-neighbor positioning algorithm were intro-duced,including the method of dynamic setting of k value,the concept of reference tags’ credibility and the algorithm of correction based on the positioning error of nearest tags.The algorithm based on the historical track of object tags was also adopted.The indoor positioning system was built with time-division multi-use antennas connected to its RF-ports.The visual software was also developed based on the algorithm proposed.Positioning accuracy and stability in complex environments were proved by experiments to be better than that of the existing algorithm.